1995
DOI: 10.1111/j.1751-1097.1995.tb05252.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Drug Photosensitization 7. Photocleavage of Dna Sensitized by Suprofen

Abstract: Ultraviolet-A irradiation of a suprofen (2-[4-2(2-thenoyl) phenyl]propionic acid) (SPF) buffered solution (pH 7.4) in the presence of supercoiled pBR322 DNA leads to single strand breaks with the formation of an open circular form and subsequent linearization of the plasmid. On the basis of agarose gel electrophoresis data of samples irradiated in an air-saturated solution or in an oxygen-modified atmosphere, and the effects of sodium azide, D20, mannitol, copper(II), superoxide dismutase, 2-H-propanol, defero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…[7] For instance, the nonsteroidal, anti-inflammatory 2-arylpropionic acids are known to photosensitize DNA damage. [8][9][10][11][12][13] Specifically, naproxen (NAP, 6-methoxy-a-methyl-2-naphthaleneacetic acid) has been demonstrated to photoinduce single-strand breaks, [14,15] which could be facilitated by a noncovalent drug-DNA interaction. [16] However, NAP does not significantly photosensitize the formation of cyclobutane pyrimidine dimers in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[7] For instance, the nonsteroidal, anti-inflammatory 2-arylpropionic acids are known to photosensitize DNA damage. [8][9][10][11][12][13] Specifically, naproxen (NAP, 6-methoxy-a-methyl-2-naphthaleneacetic acid) has been demonstrated to photoinduce single-strand breaks, [14,15] which could be facilitated by a noncovalent drug-DNA interaction. [16] However, NAP does not significantly photosensitize the formation of cyclobutane pyrimidine dimers in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] For instance, a number of nonsteroidal anti-inflammatory drugs (NSAIDs) are known to photosensitize DNA damage. [19][20][21][22] Hence, modified nucleosides containing key substructures present in drugs and nucleic acids can be relevant models to study the excited-state interactions and the primary photophysical/photochemical processes underlying drug-mediated photoreactions of DNA and their photobiological consequences. [23] In particular, they could help to gain some insight into the chemical Abstract: Time-resolved and product studies on the synthesized dyads 1 and 2 have provided evidence that the benzophenone-to-thymine orientation strongly influences intramolecular photophysical and photochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…[7] On the other hand, free radicals formed upon photodegradation of SPF and singlet oxygen were observed to act as a photosensitizer for some biological substrates both in vitro and vivo [8] that can induce red blood cell lysis, [9] photodynamic lipid peroxidation [10] and DNA photocleavage. [11] A number of investigations have been done to attempt to better elucidate the mechanism(s) that cause SPF's phototoxicity and to explore the its photochemistry characteristics in aqueous solution, [9,10,[12][13][14][15] and these mechanisms are summarized in Scheme 1. Steady-state studies have concluded that the major photochemical reaction in aqueous solution at neutral pH is decarboxylation, and p-ethylphenyl 2-thienyl ketone (ETK), p-acetylphenyl 2-thienyl ketone and p-(1-hydroxyethyl) phenyl 2-thienyl ketone were isolated as the final products, the ETK is the largely dominant product.…”
Section: Introductionmentioning
confidence: 99%